ECONOMIC AND GEOGRAPHICAL PROBLEMS OF EFFECTIVE IMPLEMENTATION AGRO-INDUSTRIAL POTENTIAL OF THE STEPPE LANDSCAPE KRASNODAR TERRITORY - Viktor Nikolaevich Tyurin; Indira Dzhamaldinovna Ayubov; Anton Dmitrievich Vivchar (Вестник Северо-Кавказского федерального университета)
This article deals with the problems of the agricultural potential of the steppe landscapes of the Krasnodar Territory. Identified weaknesses and presented ideas to solve them, which will increase the efficiency of agricultural potential.